Criticalities in the NZEB retrofit of scholastic buildings: analysis of a secondary school in Centre Italy. (December 2017) - Testi, Daniele; Rocca, Michele; Menchetti, Elena; Comelato, Simona
Abstract: In Italy, the recast of the European Directive on Energy Performance of Buildings (2010/31/EU) is implemented with specific definitions and deadlines for Nearly Zero Energy Buildings. We focus our attention on schools, not only for their social importance and high visibility, but also because in the next future a significant share of these buildings is likely to undergo refurbishment for different purposes than the energetic one. We start to analyze the criticalities associated with the current Italian legislation on NZEBs by means of a bottom-up approach: we choose a benchmark secondary school (located in Pisa, hosting about 750 students) and perform an accurate energy audit of the building system, together with an energy and economic simulation of an NZEB retrofit. More in detail, we present the case study and explain its choice as an appropriate representative of the existing scholastic buildings in Centre Italy; besides, we build two concurrent energy models, based on tailored and asset rating methods, we propose technically-feasible actions for deep renovation, and simulate, for both models, the associated energy and economic savings after 20 years of use. We observe long payback periods of the retrofit measures, due to low yearly energy uses in the existing configuration. Based on these results, we attempt to extend to a more general level the considerations on strengths and weaknesses encountered in the present application of the Italian regulation on NZEBs.